Wingbearer Saga : Wingborn - Book 2 - Liu, Marjorie M.; Kum, Grace; Issakhanian, Teny (New York : Quill Tree Books, an imprint of HarperCollins Publishers, 2024)
In this spectacular graphic novel sequel, New York Times bestselling author Marjorie Liu returns to the epic setting of Wingbearer, following Zuli and her friends as they continue their quest to save the world's magic. After her encounter with the Witch-Queen, Zuli is shaken--but feels more determined than ever to find out what's happening to the bird spirits. Armed with new information about her identity, she mounts a daring escape from a merchant airship and takes off with Frowly and Orien by her side. But the more she tries to solve the mysteries swirling around herself, the more she's drawn to legends about the mythical Siric, who have long since disappeared from the world. Zuli might be prepared to take on new challenges, along with the new allies she meets, but is she prepared to go farther than ever before to confront the universe's broken magic
Junior Library Guild
Ages 7-11.
Grades 3-6.
A Junior Library Guild selection (JLG)
Keywords: Graphic novels; Identity (Psychology) -- Comic books, strips, etc; Identity (Psychology) -- Juvenile fiction; Imaginary places -- Comic books, strips, etc; Imaginary places -- Juvenile fiction; Magic -- Comic books, strips, etc; Magic -- Juvenile fiction; Graphic novels; Identity -- Fiction; Imaginary places -- Fiction; Magic -- Fiction; Graphic novels; Identity (Psychology) -- Fiction; Imaginary places -- Fiction; Magic -- Fiction; Graphic Novel